Why not join the Roman Catholic Church? - Cornelis van der Kooi (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2021)
The title of this contribution is purposefully ambivalent.  It can be read as a rhetorical question: when there are so many good reasons to join the church of Rome, why should Protestants refrain from taking this step? The most important historical reason for the Reformation was the state of the church: the authority of the office, and the episcopacy were spoiled by abuse of that power. The access to Christ and his grace were blocked. To what degree is this reproach still viable? In recent years, from a Reformed and evangelical perspective, there have been many changes in that Church that have caused a rapprochement, and that have prompted many Protestants to become Roman Catholic. However, the title can also be read differently: as an argumentation against joining the Roman Catholic Church.  Accordingly, this chapter will elaborate upon both possibilities and offer a number of remarks on the choice itself.